Budidaya Ikan Nila (Oreochromis niloticus) Dengan Pemberian Pakan Mandiri di Desa Pulau Komang Sentajo, Kuantan Singingi Provinsi Riau - Mulyadi, Mulyadi; Pamukas, Niken Ayu; Adelina, Adelina; Suharman, Indra; Darfia, Novreta Ersyi; Kurniawan, Mhd Andry (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The production of tilapia (Oreochromis niloticus) carried out by cultivators in Komang Sentajo Island Village, Kuantan Singingi has not been optimal and has not been able to meet consumer needs. One of the causes of low fish production is because fish farmers are unable to provide artificial feed (pellets) continuously so that fish are thin and fish growth is relatively slow. The purpose of this Community Service activity is to improve the knowledge and skills of the people of Komang Sentajo Island Village to make pellets independently with good and correct techniques and apply them to tilapia cultivation so that it becomes a sustainable entrepreneur. The service activities carried out were the delivery of materials and counseling about making independent fish feed in the form of pellets using local ingredients that are cheap but of good quality. Then the practice of making fish feed is also carried out. The results of the evaluation of the implementation of the activity showed that 70% of the participants agreed and 30% of the participants strongly agreed that the material and practice of making fish feed were easy to understand so that the community was able to do it themselves. In addition, activities can be carried out with adequate and simple facilities and infrastructure with a percentage of 80% of participants agree and 20% strongly agree.